2020
DOI: 10.3389/fonc.2020.578888
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine in Oncology: Delivering on an Overdue Promise in the COVID-19 Era

Abstract: Telemedicine has historically been underutilized in medicine broadly, and specifically in oncology, despite the general availability of the needed infrastructure to offer it as a platform for remote care. The COVID-19 pandemic posed new risks of infection exposure and potentially life-threatening complications, particularly in patients with cancer, created a new setting for cancer care ideally suited for the rapid roll-out of telemedicine for patients with cancer who need regular follow up but in whom live vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 3 publications
0
14
0
1
Order By: Relevance
“…HPPs may need additional resources to deliver telehealth effectively. HPP-facing tools [ 58 , 59 ] may be helpful in providing education on “webside manner” and implementation checklists [ 58 , 59 ]. HPPs at Moffitt indicated a need for guidance on the optimal way to conduct a telehealth visit (eg, lighting and eye contact), similar to other studies [ 40 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…HPPs may need additional resources to deliver telehealth effectively. HPP-facing tools [ 58 , 59 ] may be helpful in providing education on “webside manner” and implementation checklists [ 58 , 59 ]. HPPs at Moffitt indicated a need for guidance on the optimal way to conduct a telehealth visit (eg, lighting and eye contact), similar to other studies [ 40 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, other studies have shown that video consultation services, which provide a face-to-face interaction with the patient are more likely to be accepted than other telehealth services such as telephone-based or text messaging services. 17 Owing to the COVID-19 pandemic, telemedicine services have gained more usage among health care workers in all areas of medicine, including gastroenterology, 18 pediatrics, 19 oncology, 20 urology, 21 ophthalmology, 22 endocrinology, 23 and even palliative care. 24 Sofía's Coronaid was mainly focused on primary care consultations, including internal medicine and pediatrics.…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 34 , 35 The analysis we have reported here further supports these arguments. The increased adoption of telemedicine in oncology as a result of the pandemic 36 may have a significant role to play in this regard, providing dual advantages of both safety and reassurance for participants, and the elimination of distance as a prohibiting factor to study recruitment (for some studies). Indeed, the qualitative study that we are conducting based on this analysis is making full use of remote meetings to interview participants.…”
Section: Discussionmentioning
confidence: 99%